School Factors Influencing Indonesian Student Reading Literacy based on PIRLS Data 2006 and 2011 - Ratri, Safitri Yosita (Proceeding of International Conference on Teacher Training and Education, 2016)
The study was aimed at (1) examining school factors (school sector, teaching and instruction, schoolresources and technology, school climate, school teachers and leadership activities) influenced readingliteracy, and (2) investigating how the factor interacts with reading aspects (reading experience, process and comprehension, and reading attitudes and behaviours). The study used Progress in International Reading Literacy (PIRLS) 2006 and 2011 data that was categorized as secondary data. The study was quantitative research and employed Rasch and hierarchical linear modelling (HLM) analyses. The subjects of data 2006 were 4774 and 2011 were 4779 Primary-School students nested within 158 schools sampled using a random sampling technique. Findings of the study revealed that only some school factors were influential. There were identifiable significant correlations between reading literacy and school factors such as school sector and teaching instruction in 2006, and between school sector, teaching instruction and leadership activities in2011.